PENERAPAN KONSELING KELOMPOK TERHADAP PENURUNAN PERILAKU AGRESIF SISWA SEKOLAH MENENGAH PERTAMA - Fifqi Alrais Siswanto; Suroso; Sahat Saragih (LP2M Universitas Ibrahimy, 2020)
Adolescence is a time when someone has negative behavior, a difficult phase for children and parents. Emotional imbalance and instability in many ways manifest itself at this time. Emotional inconsistency in adolescents causes adolescents to act responsively such as aggressive, rebellious, stubborn, annoying behavior, which results in social problems in interacting with those around them. The aggressive behavior of students in schools has become a universal problem, and is likely to increase recently. The purpose of this study was to see the application of group counseling to decrease the aggressive behavior of high school students. Another objective of the study is to examine the differences in the application of group counseling before and after treatment. Purposive sampling and aggressive scales were used in this experiment, to obtain 20 samples consisting of 10 students in the control group and 10 students in the experimental group at SMP Negeri 13 Surabaya who were recorded as having committed aggression at school. The rule used is a quantitative approach to analyzing data. The results of the field survey showed that students often protested and disrespected teachers, cursed, cursed, made chaos, made noise, said indecent words, and lied. By utilizing group dynamics, the authors provide group counseling interventions to reduce students' aggressive behavior. From the results of the study, it is proven that group counseling has an effect on decreasing aggressive behavior of junior high school students.